2006
DOI: 10.1016/j.schres.2006.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Differing correlates for suicide attempts among patients with schizophrenia or schizoaffective disorder in India and USA

Abstract: Background-Suicide is one of the most common causes of death among persons with schizophrenia. Differing risk factors have been identified in published studies. The differences may have arisen because a uniform set of variables was not analyzed. Alternatively, the nature and effect of risk factors may vary in different settings. To test these possibilities, we investigated the same set of variables in two independent cross-national samples ascertained using identical protocols.Methods-Patients with schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 33 publications
2
19
2
Order By: Relevance
“…This is comparable to the findings by Bhatia et al (2006) from the same center nine years ago, where they reported a prevalence of around 23% as opposed to 20–40% from world literature (Pompili et al, 2007). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is comparable to the findings by Bhatia et al (2006) from the same center nine years ago, where they reported a prevalence of around 23% as opposed to 20–40% from world literature (Pompili et al, 2007). …”
Section: Discussionsupporting
confidence: 87%
“…From mean of attempters and nonattempters, effect size was calculated as 0.66. Considering the prevalence of suicide attempters in India as 30% in schizophrenia/schizoaffective disorders (Bhatia et al, 2006), sample size was calculated using G power (http:/www.surveysystem.com/sscalc.htm), by taking alpha = 0.05 and power = 90%. The method was used for t -test (Means: Wilcoxon-Mann-Whitney Test, two groups).…”
Section: Sample Sizementioning
confidence: 99%
“…An earlier study from the same centre had reported 23.3% of attempted suicides among schizophrenia participants (Bhatia et al, 2006), they had included both schizophrenia and schizoaffective disorder while ours was a sample of schizophrenia participants only. Additionally, we included only those who reported clear intentionality and lethality.…”
Section: Discussionmentioning
confidence: 89%
“…Based on this information, consensus diagnoses were established by certified psychiatrists and psychologists using DSM IV criteria. Inter-rater and inter-site diagnostic reliability was checked throughout the study and Kappa values of 0.8 or greater were aimed for (Bhatia et al, 2006). …”
Section: Methodsmentioning
confidence: 99%